OPTICAL DIFFRACTION STUDIES OF CRYSTALLINE STRUCTURES IN ELECTRON MICROGRAPHS - Sternlieb, Irmin; Berger, Jacob E. (The Journal of cell biology, 1969)
Unit cell dimensions of mitochondrial crystals were determined by optical diffraction analysis of electron micrographs of human liver biopsy specimens. Identical unit cells were found in pathologic material obtained from six patients with Wilson's disease, from one patient with sickle-cell hepatitis, and from two normal subjects. These measurements led to the conclusion that the crystals observed in patients and in normal subjects were probably chemically identical. Furthermore, the relatively large size of the unit cell limits the choices for its constituents to phospholipid micelles or to relatively large protein molecules.